Transexualidades, desconstrução de paradigmas e políticas públicas de saúde no processo transexualizador do SUS - Melo, Ana Luisa Almeida (2024)
The transgender population demands the understanding that there is a historical process of denial, discrimination and pathologization aimed at the search for adaptation to the standards of a cisgender, binary, heterosexual, heteronormative and patriarchal society, protected by a biologicalist and moralist vision. The study aims to understand the experiences of transgender people and health professionals in the transsexualization process. A qualitative study, based on the ethnographic method, with data analyzed from interpretative anthropology and discourse analysis, carried out at the Trans Space for Reception and Care for Transsexual and Transvestite people at the Hospital das Clínicas of the Federal University of Pernambuco, using techniques as data collection, participant observation, field diary, in-depth interviews with trans people and health professionals who work in the transsexualization process. The results point to the demand for a logic of multidisciplinary and intersectoral care that seeks, in a shared way, to build debate, placing people in collective spaces for the production of care and policies. It requires action that understands that we are in a counter-hegemonic movement that requires tensioning the normality imposed on these people and strengthening the social movement in the fight for the redefinition of practices, respect and guarantee of health rights for trans people, among them the access to health services and respect for the social name. With a view to intersectorality and decentralization of health actions aimed at transsexuality. The importance and representation of the social name in the self-designation of trans people, of the ICD-11 in the depathologization process, of the need to review Ordinance No. 2,803/2013 and the establishment of a process of permanent health education for the re-signification of health care practices for the transsexual population, in addition to expanding the health care network for the trans population. Finally, studies addressing the health of the trans population come to strengthen the fight for social equity and reparation in the face of violence, invisibilization and denials suffered by these people, they come to awaken and enhance a respectful, integral and constructive logic of care beyond offering procedures, care that builds, collaboratively, in a dialogical and co-participatory process people outside the perverse logic of moralism, framing, biopower and pathologization that has affected transsexual people.